Protein requirements of growing steers limit-fed corn-based diets - Wessels, R.H.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Seven steers (513 lb) were used in an experiment to investigate optimal levels and sources of protein in diets limit-fed to allow gain of 2.2 lb/day. Treatments were: a negative-control diet (urea; supplemented, 11.7% crude protein) and six diets containing either 13.5, 15.4, or 17.2% crude protein with either solvent-extracted (SSBM) or expeller-processed (ESBM) soybean meal, in which the soybean meal replaced corn in the control diet. Diets provided 75, 87.5, 100, or 112.5% of estimated crude protein requirement for a gain of 2.2 lb/day. The basal diet contained 83% rolled corn, 15% alfalfa , and .2% urea. Nitrogen (N) retention was increased linearly (P<.01) by SBM addition with no differences between sources. Because N retention increased to the highest level offered, the steers apparently required more protein than estimated by the 1984 National Research Council' s Nutrient Requirements of Beef Cattle.
Keywords: Beef; Protein requirements; Restricted feeding; Steers